Environmental & architectural phenomenology. Vol. 14, issue 2 - (:unkn) unknown (Kansas State University. Architecture Department, 2003)
Vol. 14, No. 2, Spring 2003 (includes “items of interest,” “citations received,” book review of Shierry Weber Nicholsen's The Love of Nature, and essays by Dru Clarke, Matthew Day & Enku Mulugeta Assefa).
Keywords: Environmental psychology - Periodicals; Human beings - Effect of environment on - Periodicals; Architecture - Environmental aspects - Periodicals; Architecture - Human factors - Periodicals; Architecture - Psychological aspects - Periodicals; Phenomenology - Periodicals